Puff and Rose - Wurfel, Marlene (My University, 2017)
This is a Tales from the Lilypad remix of the Puff the Magic dragon song by Peter Yarrow and Leonard Lipton popularized by the musical group Peter, Paul and Mary in a 1963 hit. In this retelling by Marlene Wurfel, a modern little girl named Rose finds Puff hidden in a cave in the land called Honalee. This episode features an acoustic guitar version of the song Puff the Magic Dragon by Jorge Nolla. His website is: http://profdeguitare.com/
Keywords: storytelling; children's stories